Next Generation of Information Technology in Educational Management 10th IFIP WG 3.7 Conference, ITEM 2012, Bremen, Germany, August 5-8, 2012, Revised Selected Papers - Passey, Don.; Breiter, Andreas; Visscher, Adrie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the 10th IFIP WG 3.7 Conference on Information Technology in Educational Management, ITEM 2012, held in Bremen, Germany, in August 2012. The 16 revised full papers presented were carefully reviewed and selected. The papers offer an outstanding overview of the contemporary field of information technology in educational management. They focus on four key questions: Why do we need new educational management information systems? What issues face those developing new educational management information systems? What new educational management information systems are being developed? What educational management systems are already in place?
The Effects of Training School Staff for Utilizing Student Monitoring System Data -- At the Heart of the Next Generation of Information Technology in Educational Management -- The Use of Data across Countries: Development and Application of a Data Use Framework -- Computer-Based Large-Scale Assessments in Germany -- What Needs to Be Done for Successful E-Assessment Implementations? -- Investigation of the Knowledge Management Process of Schools in Turkey -- Knowledge Management in University Administration in Malaysia -- Socio-technical Gaps Exposed by the United States Department of Education$1 (Bs Teacher Incentive Fund Grant Program -- Monitoring User Patterns in School Information Systems Using Logfile -- Data Sharing between Local and National Governments for the Benefit of the Citizen: Online Free School Meals as a Transformational Project -- Refurbishment Informational School Architecture: A Base to an Educational Information Service -- Finding a School Technological Partner: A Multi-criteria Method for School Information System Producer Selection -- Reorganization and IT Implementation in Campus Management: The Project (3z(BPuL(3y (Bat RWTH Aachen University -- Educational Management Systems in Secondary Education in Hordaland County, Norway: Positional Paper -- The Ultranet and School Management: Creating a New Management Paradigm for Education -- Pupils$1 (BData: Implementing a Management Information System to Optimise Planning in Berlin Schools.s
Keywords: Computer science; Education; Computer Science; Computers and Education; Computers and Society; User Interfaces and Human Computer Interaction